2016
DOI: 10.17219/acem/31239
|View full text |Cite
|
Sign up to set email alerts
|

Large Bowel Genetic Background and Inflammatory Processes in Carcinogenesis – Systematic Review

Abstract: Colorectal cancer (CRC) has become the third most common cancer in developed countries. Each year more and more people die from CRC. CRC is also one of the most effectively studied topics in recent years. It has been found that the key phenomena in CRC development are genetic and inflammatory processes. Well-known genetic bases for the carcinogenesis of CRC include chromosomal changes characteristic of the chromosomal instability pathway which correlates with specific and well-defined genetic alterations (such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…37 Tumor-associated macrophages (TAMs) are one of the sources of cytokines, and their released IL-10 levels increase in patients with CRC, especially in advanced stages. 65 Yan et al found a correlation between a high TAM count in gastric cancer and its progression, related to EMT. 66 IL-4, one of the anti-inflammatory cytokines produced by T cells, inhibits the expression of E-cadherin and carcinoembryonic antigen (CEA), and its levels are increased in patients with CRC compared to healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…37 Tumor-associated macrophages (TAMs) are one of the sources of cytokines, and their released IL-10 levels increase in patients with CRC, especially in advanced stages. 65 Yan et al found a correlation between a high TAM count in gastric cancer and its progression, related to EMT. 66 IL-4, one of the anti-inflammatory cytokines produced by T cells, inhibits the expression of E-cadherin and carcinoembryonic antigen (CEA), and its levels are increased in patients with CRC compared to healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although genetics likely play an important role in tumorigenesis, the inflammatory process is initiated by the movement of innate immune system cells to the microenvironment, followed by the secretion of proinflammatory cytokines, growth factors, and reactive oxygen species, causing DNA damage and promoting neoplastic development, as has been found in many tumor types [6]. Our multivariable analysis revealed that five independent baseline factors (neutrophilia, thrombocytosis, hypoalbuminemia, body mass index <30 kg/m 2 , and the absence of lung metastasis) were able to predict individual outcome not only in patients with KRAS+ / TP53+ mutant cancer who had received therapy in a phase I clinical trial, but also in those who had not received therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, KRAS mutation alone, which occurs in the early process of tumorigenesis, is not sufficient to induce malignant transformation of normal epithelial cells [5, 6]. Additional loss of tumor suppressor genes, such as TP53 [7, 8], is required for cancer development, which arises through sequential accumulation of oncogenic mutations and loss of tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%
“…Another important cytokine is IL-4. It is secreted by activated T-cells and is associated with CRC progression [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%